unter Mitarbeit von Alfred Bammesberger, Heiner Eichner, Claus Haebler, Fritz Lochner von Hüttenbach, Manfred Mayrhofer, Heinz Dieter Pohl, Jochem Schindler, Wolfgang P. Schmid, Rüdiger Schmitt und Werner Thomas, Indogermanische Chronik 32b - Peters, Martin
ersch. 1988; Fortsetzung von 48:1563 und 1564.